Effects of wall waviness and temperature variations on the fluid flow and natural convection in an inclined corrugated channel - Amini, Meysam; Najafi, Mohammad; Dorosti, Qaran; Biglarian, Hassan; Ghasemi, Esmaeil (International Journal of Applied Mathematical Research, 2015)
A parametric study involving the effects of some combinations of parameters, in particular, different combinations of the Rayleigh number, amplitude, temperature, and inclination angle of a two-dimensional long wavy-walled channel on a laminar incompressible fluid flow and natural convection within the channel is performed. The considered channel has an undulated wall as one side of the channel, and a parallel flat wall at a differentially different temperature as its counterpart. The channel sustains variable inclination angle, variable wavy wall amplitude, and variable temperature-difference between its two walls. A perturbation technique in terms of the small waviness of the undulated wall is performed to obtain a set of non-linear ordinary differential equations for the main flow and its perturbations. Solving this set of equations determines the streamline and temperature profiles for the imposed varying parameters. The results reveal that the fluid velocity along the channel axis increases with increasing the Rayleigh number, but decreases with increasing the channel inclination angle. The results also show that eddies appeared due to the steep undulations intensify as the temperature-difference between the two channel walls increases. The veracity of the present work is demonstrated through comparing the obtained results with those available in the literature.